Social media users' free labor in Iran: Influencers, ethical conduct and labor exploitation - Mirghaderi, Leilasadat (Frontiers in Sociology, 2022)
As social media sites are penetrating our daily lives in an ever-increasing manner, there is a need to revisit and reexplore the theoretical concepts that have gone through paradigm shifts due to the influence of these platforms. In this regard, audience labor theory, which was originally conceptualized in the context of mass media, needs to be reexamined as the divide between production and consumption is getting narrower. Users are no longer passive consumers since social media sites have reduced the cost of production and resulted in the advent of the term “prosumption.” In such a case, as production involves performing work and results in surplus-value, it needs to be investigated whether users are being exploited for the free work they provide on these platforms. From the several identified forms of digital labor, I will focus on the concept of audience labor. To this end I will focus on identifying labor strategies that Iranian Instagram influencers employ; these strategies involve exploiting their followers to perform tasks that produce fame and visibility as well as monetary gains but leave the users uncompensated for the work they have performed. By conducting content analysis of the 2,130 stories created by 71 Iranian Instagram influencers, this study will identify the strategies that these influencers use to exploit their followers.